Design, fabrication and testing of small scale turbine jet engine - Mohamad Ridhwan, Raja Mohd (2012)
A turbine jet engine comprises of four main parts, which are a compressor, a combustion chamber, a turbine and an exhaust nozzle. Turbine jet engine operates at an open cycle called a jet propulsion cycle. A small-scale turbine jet engine comprises of the same element as the gas-turbine engine but in a smaller scale. Both engines differ in utilization and purpose of its production. Turbine jet engines were constructed mainly for air transportation while the small-scale turbine jet engines are developed for a wider purpose, ranging for research activity to hobbyist enthusiastic. Hence, this thesis encompasses the design, fabrication, and testing a small-scale turbine jet engine. The engine was derived from an automobile turbocharger, which provided the turbine and compressor component. A combustion chamber was design and fabricated. Engine support system comprised of ignition, lubrication and fuel delivery system were installed at the engine. The engine assembly was mounted in a test setup. Thermocouples were installed at three different stations on the engine flow path to measure the temperature. Fuel regulators were utilized to measure the fuel flow. The engine was started using a specific procedure until it self-sustained. During testing, the engine was only able to self-sustain approximated for 10 seconds at kg/s fuel mass flow rate. Troubleshooting and analysis regarding the failure of the engine was done. Analysis shows that there are four possible factors involves, namely, the uses of LPG fuel, large pressure drop at the exit of combustion chamber, low pressure pump and leaking at the turbocharger. Four recommendations were made for further studies, which are, utilize a brand-new turbocharger for the engine, use a pure propane gas as a source of fuel, avoid uses of pipe flange at the combustion chamber and utilize a higher pressure pump for lubrication system. Further modification was not made due to time and cost limitation.